The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/3-540-31293-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Defects and Self-Compensation in Semiconductors

Abstract: Defect formation and doping limits in semiconductors are discussed in terms of the amphoteric defect model (ADM). It is shown that the nature of defects, acceptor-like or donor-like, depends on the location of the Fermi energy relative to a common energy reference, the Fermi level-stabilization energy. The maximum free electron or hole concentration that can be achieved by doping is an intrinsic property of a given semiconductor and is fully determined by the location of the semiconductor band edges with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The amphoteric native defect model proposed by Walukiewicz [87][88][89] and experimental DFT calculations suggest that with heavy n-type doping the Fermi level shifts toward the conduction band and there is a resultant decrease in the enthalpy of formation for negatively charged V III . 75,90,91 The formation energy of these defects is dependent on the background electrical characteristics such that any dopant species which can cause the requisite Fermi level shift would result in lowering of the formation energy of vacancies.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (5) Q12mentioning
confidence: 99%
See 1 more Smart Citation
“…The amphoteric native defect model proposed by Walukiewicz [87][88][89] and experimental DFT calculations suggest that with heavy n-type doping the Fermi level shifts toward the conduction band and there is a resultant decrease in the enthalpy of formation for negatively charged V III . 75,90,91 The formation energy of these defects is dependent on the background electrical characteristics such that any dopant species which can cause the requisite Fermi level shift would result in lowering of the formation energy of vacancies.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (5) Q12mentioning
confidence: 99%
“…111 Dopant-defect complexing seems to provide the best explanation of the observed equilibrium electrical activation limits 89,[112][113][114][115] and diffusion phenomenon in n-InGaAs substrates and there is a large body of experimental evidence suggesting that high vacancy concentrations exist in heavily n-type GaAs substrates.…”
Section: Concentration Dependent Si Diffusion In Ingaas Andmentioning
confidence: 99%
“…Thus, more donors will form increasing the degree of compensation. Such a behavior can be described by the Fermi-level stabilization model [127][128][129] and is usually observed as an off-leveling of charge carrier concentration with increasing dopant concentration or by the fact that semiconductors can be doped only p-type or n-type [130,131]. The effect has been observed till now as the self-compensation of extrinsic dopants by native defects.…”
Section: Self-compensationmentioning
confidence: 99%
“…Possibly present trap states in the bandgap would also simply be filled or emptied upon doping. However, it is well known that charging of semiconductors can result in the formation of charge-compensating defects . For semiconductor nanocrystals such defects most likely appear on the surface in the form of local reduction/oxidation of surface atoms or the formation of dimers .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that charging of semiconductors can result in the formation of charge-compensating defects. 28 For semiconductor nanocrystals such defects most likely appear on the surface in the form of local reduction/oxidation of surface atoms or the formation of dimers. 29 For example, Du Fosséet al showed in a computational study that Cd-based QDs without dangling bonds are stable up to a charge of one electron but form trap states after injection of more electrons.…”
Section: Introductionmentioning
confidence: 99%